O conceito de amor em Emmanuel Lévinas - Lima, Vicente Beur Miranda (2007)
The ethic discussion in the last time has roused a great interest in many thinkers such as Ernest Thungendart, Jurgen Habbermas, Jacques Derrida, Rosmini, Bonhoefer, Guardini, Mancini. They try to put out this discussion at the present day, beside the new philisophic tendencies as: Language Philosophy, Knowledge Theory and Politic Philosophy. Among these thinkers, it has specifically in Emmanuel Levinás , a new proposal for ethic. The present paper intends to present this new proposal clearly, that in its own way break up with those others, at the same time that it goes to another point of reference to think about the real ethic, that comes from another one. According to Levinás, the reference point of ethic is not in a transcendentalism of I must , but it is in the relationship of face to face that happens when the other person is next to. This is the way how Lévinas excels the other types of ethic, because they are still in an ontologic horizon. At the same time, with this finality, it has as a main point in research, investigate the concept of Love in this new ethic scenery that Lévinas proposes. Check up about: the context, through Lévinas itinerary existential-philosophic, where it can be noted in a strong way the influence of Judaism in his intellectual formation; the dialogue with names that belong to philosophy and that influenced his thought directly. Finally, it is going to investigate what he brought of genuine in his Philosophy, the place of Love, as a member of his Ethic of Alterity, proposing a change in the philosophy view, that is, love for knowledge, to a Knowledge of Love